Changes in blood plasma vitamin E and some biochemical parameters levels during different phases of pregnancy and at parturition in Awasi and Akkaraman ewes - Naziroglu, M; Cay, M; Aksakal, M (Scientific Technical Research Council Turkey, 1997)
In this study, plasma levels of vitamin E, cholesterol, urea nitrogen, total protein, creatinine, zinc and copper were investigated in Awasi and Akkaraman ewes during different phases of pregnancy and at parturition. Thirty Awasi and thirty Akkaraman ewes which have been fed on same ration and kept in same condition were used. The blood were removed before, during pregnancy (1st, 2nd, 3th, 4th, 5th months) and also at 7th day of parturition from all of sheep. Vitamin E, cholesterol, urea nitrogen, total protein, creatinine were measured in all plasma samples. In addition, plasma zinc and copper status were determinated only before and after parturition. In pregnancy, the levels of plasma vitamin E, urea nitrogen, cholesterol and total protein were decreased compared to before pregnancy. However, after parturition, the levels of vitamin E were increased while others were not changed. in addition, zinc and copper levels in pregnancy were found significantly lower (P<0.01) than after parturition. However, no significant differences were found in creatinin levels. In conclusion; we observed that vitamin E, urea nitrogen, cholesterol, total protein, zinc and copper levels were decreased in pregnancy of Akkaraman and Awasi ewes. However, creatinine level was not changed.
Akkaraman ve ivesi koyunlannda gebelik ve do?um sonrasi kan plazmasi E vitamini ile bazi biyokimyasal de?erlerdeki de?işimler
Keywords: vitamin E; urea nitrogen; cholesterol; pregnancy; ewes